Reciprocal relationship of social capital and microfinance activities in Nyanga, Zimbabwe. Issue 1 (2nd January 2017) - Mafukata, Mavhungu; Dhlandhlara, Willie; Kancheya, Grace
ABSTRACT: This article investigates the interactive reciprocal relationship of microfinance activities and social capital among members of the Kufusa Mari microfinance scheme in Nyanga, Zimbabwe. It reports on a study conducted among 146 randomly selected respondents, plus other participants selected for focus group discussions and key informant interviews. A reciprocal relationship between microfinance activities and social capital existed in this case study, but was found to be three-pronged, also involving developmental goals. The community should be encouraged to join the Kufusa Mari group scheme to promote self-initiated grassroots community development and advancement.